The Photopic Negative Response of the Flash Electroretinogram in Multiple Sclerosis - Wang, Jing (Association for Research in Vision and Ophthalmology, Inc., 2012)
PURPOSE. To use the photopic electroretinogram (ERG) to evaluate retinal function in eyes of multiple sclerosis (MS) patients with and without a history of optic neuritis (ON) and to compare the functional and structural status of the inner retina. METHODS. Full-field ERG responses to brief red flashes (0.04–2.8 cd · s/m(2)) on a rod-saturating blue background were recorded from 51 MS patients and 33 age-matched control subjects. In patients, perimetry was performed and peripapillary retinal nerve fiber layer thickness (RNFLT) was assessed by optical coherence tomography (OCT) and scanning laser polarimetry (SLP). MS eyes were separated into groups: “ON >6” months (n = 25), “ON <6” months (n = 29), and “no ON” (n = 33) based on positive or negative history of ON and time since the last episode. Thirteen ON<6 eyes were re-evaluated 1 year later. RESULTS. PhNR amplitudes were lower in ON>6, ON<6, and no-ON eyes (mean ± SD, 17.3 ± 7.6, 16.0 ± 6.5, and 23.8 ± 9.3 μV, respectively), than in control eyes (29.8 ± 6.5 μV; P < 0.001) for a standard stimulus of 1.42 cd · s/m(2); a- and b-wave amplitudes were unaffected. PhNR amplitudes correlated with visual fields mean deviation (MD) in ON>6 (r(2) = 0.43; P < 0.001) and no-ON eyes (r(2) = 0.10; P < 0.05), with similar results for weaker stimuli. PhNR amplitudes correlated with RNFLT in ON>6 eyes: OCT (r(2) = 0.52; P < 0.0001) and SLP (r(2) = 0.51; P < 0.01); and in no-ON eyes, OCT (r(2) = 0.21; P < 0.01) and SLP (r(2) = 0.17; P < 0.05). ON<6 amplitudes did not correlate significantly with other measures, but increased after 1 year by 5.1 ± 3.1 μV (P < 0.001), visual fields MD increased by 1.8 ± 2.3 dB (P < 0.05), and RNFL loss persisted. CONCLUSIONS. Photopic ERG PhNR amplitudes in MS patients are significantly reduced in eyes with and without a history of ON.